Oscillating propagation and parametric instability of the partial Gaussian beam in graded-index multimode fibers - Yang, Guangye; Wang, Sandan; Yuan, Jinpeng; Zhou, Haitao; Wu, Zhifang; Li, Sijin (Frontiers in Physics, 2022)
We investigate the input and propagation characteristics and geometric parametric instability of the partial Gaussian beam limited by the fiber face area in a graded-index multimode fiber. The theoretical simulation shows that the energy of the partial Gaussian beam and the coupling efficiency of the fiber face are restricted by the fiber face area for the different power and spot size of the input Gaussian beam. The spot intensity pattern of the partial Gaussian beam exhibits a standard oscillating distribution in space as the beam undergoes periodic oscillations with propagation. Also, the dynamic evolution process from parametric sidebands to a supercontinuum is affected by the peak power, spot size of the partial Gaussian beam and the fiber length. Finally, the experimental output spectra with different powers of partial Gaussian beam and fiber lengths in a graded-index multimode fiber confirm the prediction of theoretical simulations. This work provides practical guidance for optimizing supercontinuum source expansion and spectral power density.